Groundwater dynamics within a watershed in the discontinuous permafrost zone near Umiujaq (Nunavik, Canada) - Parhizkar, Masoumeh; Delottier, Hugo; Cochand, Marion; Therrien, René; Murray, Renaud; Lemieux, Jean-Michel; Dagenais, Sophie; Pryet, Alexandre; Fortier, Richard; Molson, John W. H. (Hydrogeology Journal, 2020)
Groundwater distribution and flow dynamics were studied in a small watershed located in the discontinuous permafrost zone near Umiujaq in Nunavik (Québec), Canada, to assess the seasonal variations and perform a quantitative analysis of the water cycle in a subarctic watershed. Due to the complexity of the subsurface geology within the watershed, an integrated investigation was instrumental to provide a detailed understanding of the hydrogeological context as a basis for the water balance. Based on this water balance, for the two studied hydrological years of 2015 and 2016, the average values are 828 mm for precipitation, 337 mm for evapotranspiration, 46 mm for snow sublimation, 263 mm for runoff, 183 mm for groundwater exchange (losses with other aquifers outside the watershed), and 0 mm for change in water storage. Although these values likely have significant uncertainty and spatial variability, this water balance is shown to be plausible. It was also found that permafrost influences surface water and groundwater interaction, even if located in low-permeability sediments. It is expected that permafrost degradation will likely increase stream baseflow, especially in winter. La distribution et la dynamique des eaux souterraines ont été étudiées dans un petit bassin versant situé dans la zone de pergélisol discontinu près d’Umiujaq au Nunavik (Québec, Canada), afin d’effectuer une analyse quantitative du cycle de l’eau dans un bassin versant subarctique. En raison de la complexité du contexte géologique dans le bassin versant, une approche intégrée a été utilisée afin de décrire le contexte hydrogéologique nécessaire à la réalisation du bilan hydrique. Sur la base de ce bilan hydrique, pour les deux années hydrologiques étudiées en 2015 et 2016, les valeurs moyennes sont de 828 mm pour les précipitations, de 337 mm pour l’évapotranspiration, de 46 mm pour la sublimation dans la neige, de 263 mm pour le ruissellement et de 183 mm pour l’échange entre les eaux souterraines avec d’autres aquifères situés en ...